Serum and Urinary Osteocalcin in Healthy 7- to 19-Year-Old Finnish Children and Adolescents - Paldánius, Päivi M.; Ivaska, Kaisa K.; Mäkitie, Outi; Viljakainen, Heli (Frontiers in Pediatrics, 2021)
Children and adolescents have high bone turnover marker (BTM) levels due to high growth velocity and rapid bone turnover. Pediatric normative values for BTMs reflecting bone formation and resorption are vital for timely assessment of healthy bone turnover, investigating skeletal diseases or monitoring treatment outcomes. Optimally, clinically feasible measurement protocols for BTMs would be validated, and measurable in both urine and serum. We aimed to a) establish sex- and age-specific reference intervals for urinary and serum total and carboxylated osteocalcin (OC) in 7-19-year-old healthy Finnish children and adolescents (n=172), b) to validate these against standardized serum and urinary BTMs, and c) to assess the impact of anthropometry, pubertal status and body composition on the OC values. All OC values in addition to other BTMs increased with puberty, correlated with pubertal growth, which occurred and declined earlier in girls than in boys. The mean serum total and carboxylated OC and urinary OC values and percentiles for sex-specific age categories and pubertal stages were established. Correlation between serum and urinary OC was weak, especially in younger boys, but improved with increasing age. The independent determinants for OC varied, the urinary OC being most robust while age, height, weight, and plasma parathyroid hormone (PTH) influenced serum total and carboxylated OC values. Body composition parameters had no influence on any of the OC values. In children and adolescents, circulating and urinary OC reflect more accurately growth status than bone mineral density (BMD) or body composition. Thus, validity of OC, similar to other BTMs, as a single marker of bone turnover, remains limited. Yet, serum and urinary OC similarly to other BTMs provide a valuable supplementary tool when assessing longitudinal changes in bone health with repeat measurements, in combination with other clinically relevant parameters.